2012
DOI: 10.1100/2012/764563
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility Profile ofAeromonasSpecies Isolated from Wastewater Treatment Plant

Abstract: This study assessed the prevalence of antibiotic-resistant Aeromonas species isolated from Alice and Fort Beaufort wastewater treatment plant in the Eastern Cape Province of South Africa. Antibiotic susceptibility was determined using the disc diffusion method, and polymerase chain reaction (PCR) assay was employed for the detection of antibiotics resistance genes. Variable susceptibilities were observed against ciprofloxacin, chloramphenicol, nalidixic acid, gentamicin, minocycline, among others. Aeromonas is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 34 publications
6
40
0
1
Order By: Relevance
“…Instead, over 98% of tetracycline-and ciprofloxacin-resistant isolates were identified as A. hydrophila or A. veronii, and 72% of isolates that were resistant to both antibiotics were identified as A. hydrophila. The higher prevalence of tetracycline resistance than ciprofloxacin resistance among Aeromonas organisms is in agreement with other environmental and clinical studies (15,21,29,30) and highlights the antibiotic resistance in the genus, specifically among Aeromonas species that are associated with human disease.…”
Section: Discussionsupporting
confidence: 90%
“…Instead, over 98% of tetracycline-and ciprofloxacin-resistant isolates were identified as A. hydrophila or A. veronii, and 72% of isolates that were resistant to both antibiotics were identified as A. hydrophila. The higher prevalence of tetracycline resistance than ciprofloxacin resistance among Aeromonas organisms is in agreement with other environmental and clinical studies (15,21,29,30) and highlights the antibiotic resistance in the genus, specifically among Aeromonas species that are associated with human disease.…”
Section: Discussionsupporting
confidence: 90%
“…Findings of the present study are in corroboration with Schmidt et al (2001) and Igbinosa and Okoh (2012) in terms of detection of class 1 integron but contrast for Tet (C). Both authors could not detect Tet (C) in Aeromonas species; however class 1 integron gene cassette was detected.…”
Section: Discussionsupporting
confidence: 86%
“…The detection of class 1 integron indicates the potential spread of antimicrobial resistance genes within the Enterobacteriaceae family in the simulated environment. Presence of β-lactamase genes in Aeromonas has been reported by Igbinosa and Okoh (2012) which is an alarming public health concern.…”
Section: Discussionmentioning
confidence: 99%
“…However, the detection frequency of strA was lower than that reported by Wang et al (2013a). The frequency of TEM gene in Aeromonas isolates (Tables S5 and S6) was lower than that reported by Igbinosa and Okoh (2012). Lu et al (2010) reported that the CTX gene and TEM gene were dominant (22 strains) in ESBL-producing bacteria from an urban river sediment habitat.…”
Section: Args Decreased In Cultivable Heterotrophs But Increased In Smentioning
confidence: 68%